Integrating Public Theology into African theological institutions’ curricula - Sunday Bobai Agang (African Theological Journal for Church and Society)
The primary aim of this article is to argue that the curricula of many African evangelical theological seminaries are devoid of Public Theology. This lack has made it extremely difficult for the church in Africa to collapse the sacred-secular divide. As a result, our public faith does not tally with our private faith, beliefs and practices. The curriculum that our evangelical pastors get trained in lacking an important ingredient: Public Theology. As such it does not address and help its graduates to collapse the sacred-secular divide. Thus, although year in and year out our evangelical seminaries are turning out graduates, they are in much cases incapable of overcoming ethnic differences. They do not know how to reposition and transform their communities into vibrant Christian communities. They largely tend to have no clear-cut understanding of the public relevance of their Christian faith, talk less of helping their members to collapse the sacred-secular divide and become effective Christians in every sphere of public life and human endeavours.